2021
DOI: 10.1002/ldr.3963
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil phosphorus availability and associated microbial properties after chicken farming in Lei bamboo (Phyllostachys praecox) forest ecosystems

Abstract: Bamboo‐chicken farming (BCF) is a popular bamboo complex management model in Southeast Asia. However, the effects of BCF on phosphorus (P) availability and associated soil microbial communities remain poorly understood. In this study, we compared the soil properties, P fractions, phosphatase activities, and bacterial community compositions in the surface soil (0–20 cm) of a typical BCF system under different grazing densities [represented as distances of 5, 15, 25, 35, and > 60 m (control site) from the henhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Similarly, we found that within the Acidobacteria dominant genus harbored higher abundance of P solubilization and mineralization genes than other genes in both temperature and subtropical forests, especially the genus of Candidatus Solibacter and Terriglobus (Table 2). Bacteria within the Proteobacteria orders Pseudomonadales and Rhizobiales have been characterized as efficient P solubilizers that have the capacity to access smaller and less recalcitrant pool of P in soils [42] on account of their suite of P mineralization and solubilization genes [43]. Consistent with this finding, the identified Bradyrhizobium genus, the branches of Rhizobiales contained higher abundance P solubilization and mineralization genes and P uptake and transport genes (Table 2).…”
Section: P Functional Genes In Temperate and Subtropical Zonesmentioning
confidence: 56%
“…Similarly, we found that within the Acidobacteria dominant genus harbored higher abundance of P solubilization and mineralization genes than other genes in both temperature and subtropical forests, especially the genus of Candidatus Solibacter and Terriglobus (Table 2). Bacteria within the Proteobacteria orders Pseudomonadales and Rhizobiales have been characterized as efficient P solubilizers that have the capacity to access smaller and less recalcitrant pool of P in soils [42] on account of their suite of P mineralization and solubilization genes [43]. Consistent with this finding, the identified Bradyrhizobium genus, the branches of Rhizobiales contained higher abundance P solubilization and mineralization genes and P uptake and transport genes (Table 2).…”
Section: P Functional Genes In Temperate and Subtropical Zonesmentioning
confidence: 56%
“…Additionally, different restoration methods may also affect the physical and chemical properties of the soil, thereby altering the solubility and availability of potassium and subsequently affecting the soil total potassium content. Root cutting can also increase soil permeability and thus improve the circulation and metabolism of soil organic matter (OM), nitrogen (N) and phosphorus (P) by microorganisms [28,29], The lack of oxygen in soil will greatly limit the development of plant roots and microorganisms [30].…”
Section: Mechanisms Of the Effects Of Different Restoration Methods O...mentioning
confidence: 99%
“…Generally, the soil is enriched in total P but lacks available P. In soil, 95% of P is unavailable (Paola et al, 2019). P is mostly bound to minerals or occurs in organic compounds, and therefore the amount of readily accessible P is a significant constraint on agricultural output (Gai et al, 2021;Li et al, 2022). Replenishment of soil P through fertilization is common in agriculture and forestry, but the long-term sustainability of this practice is questionable (Azeez et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%